Analisis Produktivitas Tenaga Kerja Pemasangan Ubin Keramik Pada Proyek Makassar New Port - Acen Patanduk; Josefine Ernestine Latupeirissa; Herby Calvin Pascal Tiyouw (Paulus Civil Engineering Journal, 2021)
The aim of this study is to investigate the productivity capacity of the ceramic tile installation workforce at the Makassar New Port project, based on field data and the Indonesian National Standard (SNI). This research was conducted for ± 10 days in the Makassar New Port project. The objects to be studied as a source of data in this research are workmen who work on ceramic tile installation, regarding the factors that affect the performance of human resources in the field, especially on their work skills, speed, and accuracy. The observations were made per square meter of ceramic tile installation for each work item on 1 working day, while data recording was carried out per day for 6 working days. The research method used in this research is the work study method, which is a research conducted by collecting data directly from observations in the field. This research was conducted by collecting primary data which is directly examined in the field related to the research carried out as secondary data, which is called the work study method because the observational data is taken while conducting the field work. The result of this research is that the production capacity in the ceramic tile installation of the Makassar New Port project is bigger than the Indonesian National Standard (SNI), this shows that the hired workmen in the work of the retaining stone installation work is very productive.